Blended Learning: To Read or Not To Read - Tracey Ang; Melor Md Yunus (Universitas Sebelas Maret, 2018)
Malaysian school had moved on to the second shift of Malaysia Education Blueprint, which is to make sure that all students in the school are able to master the basic skills of Bahasa Malaysia and English language. The English language is not a foreign language to people in Sabah, but many Sabah's students are still struggling to learn to read English literature because most of the reading activity takes place together or happens when they are using textbook or storybook. Meanwhile, because Sabah consist of multiracial people, English language had become their third or fourth acquired language. So, it is going to be a very tough challenge for the student to learn the English language skills, especially in reading. This conceptual paper aims to discuss the advantages of blended learning in order to increase Sabah's students reading ability in English literature. The paper will debate the benefits of blended learning for reading activities and the impact of applying blended learning in reading activities, especially during the English language lesson to the students and teacher. From the discussions, hopefully, it would provide a significant insight towards applying blended learning not just to teach English literacy reading in the classroom, but also for other language skills and other subjects.